Reproductive parameters of eastern North Pacific blue whales Balaenoptera musculus - R Sears; C Ramp; AB Douglas; J Calambokidis (Endangered Species Research, 2013)
Knowledge of reproduction in baleen whales such as the blue whale Balaenoptera musculus is still limited. Here, we combined the sighting histories of 24 yr of reproductively active female blue whales from the United States (US) west coast and the Gulf of California (GoC), Mexico. The latter region is a nursing ground for some of the blue whales that feed off the US west coast during the summer months. We report here that females show site fidelity to the GoC even when not lactating. The mean calving interval based on consecutive sighting histories was 2.57 yr. Two female calves returned with their own offspring after 11 and 13 yr, indicating an apparent age of first parturition of >10 yr. While 60% of females identified in the GoC were also sighted off the US west coast, only 30% of the females from the latter area were seen in the GoC. Thus only a part of the US Californian population migrates to the GoC, suggesting the existence of additional calving and nursing grounds for this population. Despite the presence of killer whales, female blue whales presumably migrate to the GoC to benefit from high prey abundance. The lack of documented births in the GoC may indicate that female blue whales choose open, pelagic waters for calving and move to the GoC when the calves are older.